2020
DOI: 10.3390/nu12103184
|View full text |Cite
|
Sign up to set email alerts
|

Diet to Reduce the Metabolic Syndrome Associated with Menopause. The Logic for Olive Oil

Abstract: The rates of metabolic syndrome are increasing in parallel with the increasing prevalence of obesity, primarily due to its concomitant insulin resistance. This is particularly concerning for women, as the years around menopause are accompanied by an increase in visceral obesity, a strong determinant of insulin resistance. A fall in estrogens and increase in the androgen/estrogen ratio is attributed a determining role in this process, which has been confirmed in other physiological models, such as polycystic ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 117 publications
0
6
0
1
Order By: Relevance
“…Recent studies have shown that an MD reduces serum inflammatory markers as well as the incidence of stroke, CVD and breast cancer [ 138 , 139 ]. Moreover, MD was recommended as a diet that can help women with menopause-related symptoms and needs [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that an MD reduces serum inflammatory markers as well as the incidence of stroke, CVD and breast cancer [ 138 , 139 ]. Moreover, MD was recommended as a diet that can help women with menopause-related symptoms and needs [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies indicate that OT is not only a cardiovascular protective peptide but also critical for cardiovascular homeostasis and for the reduction in the severity of cardiovascular pathologies: OT treatment improves cardiac work, reduces apoptosis and inflammation and increases scar vascularization [40]. Menopause is associated with an increased risk of metabolic syndrome related to an increase in visceral obesity, a strong determinant of insulin resistance and recognized as a risk factor for cardiovascular diseases [55]. OT is involved in the regulation of eating behavior, energy expenditure, lipid metabolism and glucose homeostasis [56].…”
Section: Oxytocin As a Therapeutic Agent: Perspectivesmentioning
confidence: 99%
“…MetS refers to a collection of many variables, which include hypertension, dyslipidemia, cellular resistance to insulin, obesity, and glucose intolerance. These factors collectively elevate individuals' susceptibility to developing cardiovascular disease and type 2 diabetes [ 28 ]. The prevalence of MetS is increasing on a global scale.…”
Section: Reviewmentioning
confidence: 99%